PENGUJIAN KARAKTERISTIK POMPA SENTRIFUGAL SUSUNAN SERI DAN PARAREL DENGAN TIGA POMPA PADA SPESIFIKASI YANG BERBEDA - KRISTIAN TARIGAN (JURNAL ILMIAH KOHESI, 2020)
The objective of this final task is to know the characteristics of centrifugal water pumps using series and parallel circuits using the specifications type DK-175 Daito Kuta brand and power 0.37 Kw. Measurement of the discharge with the Flowmeter brand ZYIA and pressure using Japan pressure gauge. The circuit is also equipped with several piping equipment. Tests carried out on series and parallel circuits with variations of the valve opening respectively 340, 300, 260 and 220 for series and parallel 2 pumps, angles 340, 260, 220 and 180 for the 3 series pumps and 300, 240, 180 and 140 to parallel 3pumps. Data processing with Microsoft Excel programs and graphs. The test results show the debit value inversely proportional to the head value. The decrease in the discharge of the series averages 50% and an average parallel range of 60%, the debit value is comparable to that of the pump power value, the increase in the pump value of the series averages 60% and the average parallel range of 75%. The value of discharge is inversely proportional to the efficiency, the decrease in the series averages 20% and the average parallel range of 10% to the increased discharge.